Search for multiple resistance in maize to stem-borers under natural infestation in midaltitude intermediate maturity areas in Kenya - Gethi, M.
Sumario (En)
Ilus.; 10 ref.
Keywords: FITOMEJORAMIENTO; GERMOPLASMA; HIBRIDOS; CHILO PARTELLUS; BUáEOLA FUSCA; KENIA